Clinical Characteristics and Prognosis of Incidentally Detected Lung Cancers. (3rd February 2015) - Quadrelli, S.; Lyons, G.; Colt, H.; Chimondeguy, D.; Buero, A.
Abstract : Objective . To evaluate clinical characteristics and outcomes in incidentally detected lung cancer and in symptomatic lung cancer. Material and Methods . We designed a retrospective study including all patients undergoing pulmonary resection with a curative intention for NSCLC. They were classified into two groups according to the presence or absence of cancer-related symptoms at diagnosis in asymptomatic (ASX)—incidental diagnosis—or symptomatic. Results . Of the 593 patients, 320 (53.9%) were ASX. In 71.8% of these, diagnosis was made by chest X-ray. Patients in the ASX group were older (P = 0.007 ), had a higher prevalence of previous malignancy (P = 0.002 ), presented as a solitary nodule more frequently (P < 0.001 ), and were more likely to have earlier-stage disease and smaller cancers (P = 0.0001 ). A higher prevalence of incidental detection was observed in the last ten years (P = 0.008 ). Overall 5-year survival was higher for ASX (P = 0.001 ). Median survival times in pathological stages IIIB-IV were not significantly different. Conclusion . Incidental finding of NSCLC is not uncommon even among nonsmokers. It occurred frequently in smokers and in those with history of previous malignancy. Mortality of incidental diagnosis group was lower, but the better survival was related to the greater number of patients with earlier-stage disease.